About Carrier's Self-Trapping and Dynamical Rashba Splitting in the 2D Hybrid Perovskite (BA)2(MA)2Pb3l10 - Qi, Weiyan; Ponzoni, Stefano; Huitric, Guénolé; Gorelov, Vitaly; Pramanik, Ashim; Laplace, Yannis; Marsi, Marino; Papalazarou, Evangelos; Maehrlein, Sebastian F.; Deleporte, Emmanuelle; Mallik, Nitin; Taleb-Ibrahimi, Amina; et al. (Small, 2026)
Time- and Angle-Resolved Photoelectron Spectroscopy (tr-ARPES) is employed to monitor photoexcited electrons in the 2D hybrid perovskite (BA) (Formula presented.) (MA) (Formula presented.) (Formula presented.) (Formula presented.). Photoelectron intensity maps are in good agreement with ab-initio calculations of the band structure. The effective mass is (Formula presented.) and (Formula presented.) for holes and electrons, respectively. In the photoexcited state, spin-orbit splitting of the conduction band cannot be resolved. This sets the upper bound of photoinduced Rashba coupling to (Formula presented.) eVÅ. The correlated electron-hole plasma evolves in Wannier excitons with Bohr radius of 2.8 nm, while no sign of self-trapping in small polarons is found within the investigated time window of up to 120 ps following photoexcitation.
Publisher Copyright: © 2026 Wiley-VCH GmbH.
Keywords: 2D perovskite; band structure; exciton; Rashba; self trapping